Comparative Analysis Of Salam And Istishna' Agreements In Syariah Economic Transactions - Amanda Dinira Chandra; Amira Auni; Cindy Aulia; Muhammad Nur Iqbal (Sean Institute, 2024)
Buy and sell regards and istishna ' is law sell buy allowed in Islam, where type sell buy This You're welcome own system payment at the beginning moreover before. Research This done For know location difference draft sell buy regards and istishna '. Research This based on the results observations that discuss about draft sell buy regards and ishtisna ' in concept of Islamic religion. Research This aiming For know about understanding, basics law, conditions and pillars, implementation regards and istishna ' in Islamic Financial Institutions, as well as Views of related scholars contract regards and istishna '. The research method that the author uses use is method study library research where we search from various source reference like books, journals, and e-book. Research results show difference law sell buy regards and istishna ' from aspect understanding, basics law, and from aspect harmony and conditions. Also provide explanation to implementation contract regards and istishna ' in Islamic Financial Institutions and Views of related scholars contract regards and istishna '. According to Imam Syafi'I contract regards legitimate must fulfil condition in'iqad, condition valid, conditions muslim phew, whereas For istishna ' Some Schools Shafi'i forbid contract istishna ' adheres to the principle of qiyas, namely comparison equalize law new problem with the law that has been happen previous. Opinions of some of the Imam Shafi'i School of thought other allow contract istisna This with reason ' urf (custom) habits) that occur in the middle middle society and needs public to contract like This.